The apoptotic suppressor P35 is required early during baculovirus replication and is targeted to the cytosol of infected cells. - Hershberger, P A (1994)
The p35 gene of Autographa californica nuclear polyhedrosis virus (AcMNPV) is required to block virus-induced apoptosis. The trans-dominant activity of p35 suppresses premature cell death and facilitates AcMNPV replication in a cell line- and host-specific manner. To characterize the p35 gene product (P35), a specific polyclonal antiserum was raised. As revealed by immunoblot analyses of wild-type AcMNPV-infected cells, P35 appeared early (8 to 12 h) and accumulated through the late stages of infection (24 to 36 h). Biochemical fractionation of cells both early and late in infection and indirect immunochemical staining demonstrated that P35 localized predominantly to the cytosol (150,000 x g supernatant); comparatively minor quantities of P35 were associated with intracellular membranes. The cytoplasmic localization of P35 was independent of virus infection. The functional significance of the early and late synthesis of P35 was examined by constructing recombinant viruses in which the timing and level of p35 expression were altered. Delaying P35 synthesis by placing p35 under exclusive control of a strong, very late promoter failed to suppress intracellular DNA fragmentation and apoptotic blebbing in most cells. Thus, earlier expression of p35 was required to block virus-induced apoptosis. Site-specific mutagenesis of the p35 promoter demonstrated that low levels of P35 were sufficient to block apoptosis, whereas higher levels were required to maintain wild-type virus gene expression. Consistent with an early role in infection, P35 was also detected in the budded form of AcMNPV. Because of the lack of sequence similarity and its cytosolic targeting, P35 may function in a manner that is mechanistically distinct from other apoptotic regulators, including Bcl-2 and the adenovirus E1B 19-kDa protein.